2016
DOI: 10.21451/1984-3143-ar782
|View full text |Cite
|
Sign up to set email alerts
|

Use of glucose or BTS"! combined with DMSO or methylglycol under two different freezing protocols for the cryopreservation of sperm from the common curimatã (Prochilodus brevis)

Abstract: This study evaluated the effect of glucose or Beltsville Thawing Solution (BTS™) combined with dimethyl sulfoxide (DMSO) or methylglycol (MG) under two different freezing protocols on the kinetics and morphology of cryopreserved Prochilodus brevis sperm. The semen samples were diluted using one of four different treatments (glucose+DMSO, glucose+MG, BTS™+DMSO, and BTS™+MG), loaded into 0.25-ml straws and subjected to two different freezing processes (programmed freezing machine and dry shipper). After 10 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
0
7
1
8
Order By: Relevance
“…Existem estudos que esclarecem aspectos sobre a reprodução de P. brevis, inclusive sobre a aplicação da técnica de congelação seminal, que demonstraram a boa congelabilidade do sêmen, utilizando diluentes como a glicose [10,13,17] e a água de coco em pó (ACP-104) [4]. Porém, a coleta seminal geralmente ocorre em locais com poucos recursos laboratoriais, sendo necessária a translocação de equipamentos e mais recursos humanos em campo [21].…”
Section: Introductionunclassified
“…Existem estudos que esclarecem aspectos sobre a reprodução de P. brevis, inclusive sobre a aplicação da técnica de congelação seminal, que demonstraram a boa congelabilidade do sêmen, utilizando diluentes como a glicose [10,13,17] e a água de coco em pó (ACP-104) [4]. Porém, a coleta seminal geralmente ocorre em locais com poucos recursos laboratoriais, sendo necessária a translocação de equipamentos e mais recursos humanos em campo [21].…”
Section: Introductionunclassified
“…In this study, the addition of honey in the diluent showed no significant difference. The acceptable of spermatozoa morphological abnormalities was 20-30% (27). However, the honey addition was better when compared with the control.…”
Section: Discussionmentioning
confidence: 87%
“…Efficient cryopreservation of fish semen using MG was demonstrated in Piracanjuba (Maria, Viveiros, Freitas, & Oliveira, ). Derived from methanol (CH 3 OH) and ethylene oxide (CH 2 OCH 2 ; Viveiros, Oliveira, Maria, Orfão, & Souza, ), MG is considered a non‐toxic alcohol (Pinheiro et al, ; Takagi, Otoi, & Suzuki, ). This explains its popularity as a favourite cryoprotectant in comparison to other alcohols like DMSO (Viveiros et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…MG in concert with BTS also showed high‐quality cryopreservation of semen in Brycon nattereri (Viveiros et al, ). Pinheiro et al (), in a study using four different freezing media, observed that the MG‐containing medium with glucose shows higher motility (70%–76%) as compared to MG and BTS‐containing medium.…”
Section: Discussionmentioning
confidence: 99%